The influence of distributive justice and procedural justice on job satisfaction among workers at Aqaba Container Terminal, Jordan - Obeidat, Khalid Mohsen Ali (2016)
Human Resources Management (HRM) plays an important role in the performance and profitability of every organization. Similarly, the job satisfaction of employees is critical to the success of every organization. In the case of Aqaba Container Terminals in Jordan, many employees have been protesting their dissatisfaction on the issue of salaries and bonus payment. Therefore, this study examines the influence of distributive and procedural justice that lead to job satisfaction among workers of Aqaba Container Terminals in Jordan. Using survey questionnaires, data were collected from 200 workers of the Aqaba Container Terminals. The data were analyzed using both correlation and regression analysis. The findings of this study revealed that both distributive and procedural justice have significant influence on job satisfaction. The findings of this study theoretically contribute to explain factors that lead to employees’ job satisfaction. The practical implications of this study are evident in providing HR managers, especially in the Aqaba Container Terminals the importance of distributive and procedural justice and the reason for employees’ job satisfaction should be taken importantly